St. Vincent and the Grenadines : 2007 Article IV Consultation; Staff Report; Staff Supplement and Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for St. Vincent and the Grenadines. (IMF Staff Country Reports; Country Report, 2009)
This 2007 Article IV Consultation highlights that the economy of St. Vincent and the Grenadines is enjoying its second year of vigorous economic growth. Financial sector indicators have strengthened, but balance sheet vulnerabilities remain. Executive Directors have welcomed St. Vincent and the Grenadines' recent strong macroeconomic performance, marked by robust economic growth, fiscal consolidation, and declining debt levels. Directors have also stressed that continued fiscal consolidation is needed to lower the public debt-to-GDP ratio, and create room to raise social spending.